Cardiovascular disease in adults with a history of out-of-home care during childhood: a systematic review and meta-analysis of prospective cohort studiesResearch in context - G. David Batty; Mika Kivimäki; Ylva B. Almquist; Johan G. Eriksson; Mika Gissler; Emmanuel S. Gnanamanickam; Mark Hamer; Josephine Jackisch; Hee-Soon Juon; Markus Keski-Säntti; Chaiquan Li; Tuija M. Mikkola; et al. (Elsevier, 2024)
Summary: Background: While individuals who were separated from their biological family and placed into the care of the state during childhood (out-of-home care) are more prone to developing selected adverse health problems in adulthood, their risk of cardiovascular disease is uncertain. Our aim was to explore this association by pooling published and unpublished results from prospective cohort studies. Methods: We used two approaches to identifying relevant data on childhood care and adult cardiovascular disease (PROSPERO registration CRD42021254665). First, to locate published studies, we searched PubMed (Medline) until November 2023. Second, with the objective of identifying unpublished studies with the potential to address the present research question, we scrutinised retrieved reviews on childhood out-of-home care and other adult health outcomes. Included studies were required to satisfy three criteria: a cohort study in which the assessment of care was made prospectively pre-adulthood (in the avoidance of recall bias); data on an unexposed comparator group were available (for the computation of relative risk); and a diagnosis of adult cardiovascular disease events (coronary heart disease, stroke, or their combination) had been made (as opposed to risk factors only). Collaborating investigators provided study-specific estimates which were aggregated using random-effects meta-analysis. The Newcastle-Ottawa Scale was used to assess individual study quality. Findings: Twelve studies (2 published, 10 unpublished) met the inclusion criteria, and investigators from nine provided viable results, including updated analyses of the published studies. Studies comprised 611,601 individuals (301,129 women) from the US, UK, Sweden, Finland, and Australia. Five of the nine studies were judged to be of higher methodological quality. Relative to the unexposed, individuals with a care placement during childhood had a 51% greater risk of cardiovascular disease in adulthood (summary rate ratio after age- and sex-adjustment [95% confidence interval]: 1.51 [1.22, 1.86]; range of study-specific estimates: 1.07 to 2.06; I2 = 69%, p = 0.001). This association was attenuated but persisted after adjustment for socioeconomic status in childhood (8 studies; 1.41 [1.15, 1.72]) and adulthood (9 studies, 1.29 [1.11, 1.51]). Interpretation: Our findings show that individuals with experience of out-of-home care in childhood have a moderately raised risk of cardiovascular disease in adulthood. Funding: Medical Research Council; National Institute on Aging; Wellcome Trust.